Cooperative adaptive fuzzy control for a class of uncertain non-linear multi-agent systems with time delays. Issue 3 (3rd July 2017) - Wu, Li-Bing; He, Xi-Qin; Zhang, Da-Qing
Abstract : This paper studies the robust adaptive fuzzy cooperative tracking control problem for a class of uncertain non-linear multi-agent systems with multiple time delays and dead-zone non-linearities. First, based on the implicit function theorem, the non-affine form of the multi-agent system can be converted into the corresponding affine form. Then, using the local state information of neighbouring agents, a novel adaptive fuzzy cooperative tracking controller with the corresponding parameter-updated laws is designed based on undirected communication topologies. Furthermore, it is shown that all the closed-loop signals are bounded, and all follower nodes asymptotically tracking to the leader can be achieved in the presence of time-delayed perturbations and unknown dead-zone inputs. Finally, simulation results are given to demonstrate the effectiveness of the proposed adaptive control scheme.